The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/su13094671
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Sustainable Concrete Using Activated Sludge of Industrial By-Products

Abstract: Industrial sludge byproducts contain CaO, SiO2, Al2O3, etc. When industrial sludge is used in ready-mixed concrete, the performance of the concrete can be enhanced due to the hydration reaction. In the present study, activated sludge was used to prepare ready-mixed concrete, and its durability performance was evaluated. Once the activated sludge was used, the durability of the concrete improved. Therefore, it is suggested that activated sludge can be used in concrete mix as an admixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…DG and recycled water were utilized to partially replace cement with fly ash and blast furnace slag to prepare concrete [70]. It was shown that the addition of DG and re- DG and PG also have good applications in filling materials.…”
Section: Other Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…DG and recycled water were utilized to partially replace cement with fly ash and blast furnace slag to prepare concrete [70]. It was shown that the addition of DG and re- DG and PG also have good applications in filling materials.…”
Section: Other Materialsmentioning
confidence: 99%
“…DG and recycled water were utilized to partially replace cement with fly ash and blast furnace slag to prepare concrete [70]. It was shown that the addition of DG and recycled water resulted in a partial increase in the compressive strength of the concrete.…”
Section: Other Materialsmentioning
confidence: 99%